RELU integrated floodplain management - Morris, Joe; Hess, Tim M.; Gowing, David; Trawick, Paul; Leeds-Harrison, Peter; Blowers, Andy; Tucker, Graham (Cranfield University, 2009)
The last 25 years have witnessed a change in the priorities for the use of rural land in the United Kingdom. Whereas previously the focus was predominantly on agricultural production to achieve national self sufficiency, since the 1980s environmental objectives, such as the protection of wildlife habitats and countryside recreation, have exerted greater influence over the way land is managed.
Integrated management of floodplains